The Development of Clinical Nursing Practice Guidelines under Anesthetic Management for Vascular Access Operation in UdonThani Hospital - Niemsangtaveesang, Nunnapat; Rattanasimakorn, Supaporn (Journal of The Royal Thai Army Nurses, 2024)
This research and development is a study to develop the Clinical Nursing Practice Guidelines under anesthesia for vascular access operation. It consists of 4 phases: 1) evidence triggered phase, 2) evidence supported phase, 3) the Clinical Nursing Practice Guidelines trial phase, and 4) implementation phase and Evaluation. The sampling was 110 patients undergoing vascular access operation anesthesia. The sampling was divided into 55 patients each of a control group and experimental group, and 48 nurse anesthetists, Udonthani hospital. The research results found that there are 6 components of the Clinical Nursing Practice Guidelines: 1) training in using the guidelines, 2) assessing patient readiness before surgery, 3) preparing patients before anesthesia by providing information through video media, 4) care during anesthesia, 5) post-anesthesia care, and 6) post-operative follow-up., The nurse anesthetists were able to use the guideline in every component 100% and had the high level of satisfaction of the guideline (mean = 4.27, SD = 0.5), complications during anesthesia after using the guidelines were less common than before using the guidelines. Conclusion: Clinical nursing practice guidelines under anesthesia for vascular surgery for hemodialysis help produce good results, Therefore, it is appropriate to use it as a standard for effective nursing practice.